Effect of food on capsule and granule formulations of selumetinib - Sarit Cohen‐Rabbie; Alexandra Mattinson; Karen So; Nan Wang; Ronald Goldwater (Wiley, 2022)
Abstract Selumetinib is an oral, potent, and highly selective allosteric MEK1/2 inhibitor approved for the treatment of pediatric patients (aged ≥2 years) with neurofibromatosis type 1 who have symptomatic, inoperable plexiform neurofibromas. A granule formulation of selumetinib is under development to improve dosing precision for younger pediatric patients who may be unable to swallow capsules. This phase I crossover study investigated the effect of food on the pharmacokinetic (PK) properties of selumetinib capsule and granule formulations. Healthy male volunteers were randomized to receive selumetinib granules (25 mg) or capsules (50 mg [2 × 25 mg]) under fasted or fed conditions (a low‐fat meal). Plasma concentrations and PK parameters were determined less than or equal to 48 h postdose. Safety and tolerability were assessed. Across 24 volunteers, selumetinib was absorbed quickly, with a time to maximum concentration (Tmax) ranging from ~1-3 h. Geometric mean ratios (90% confidence interval [CI]) for maximum plasma concentration (Cmax) in the fed versus fasted state were 0.61 (90% CI 0.51-0.72) and 0.40 (90% CI 0.33-0.48) for the granule and capsule formulations, respectively, whereas geometric mean ratios (90% CI) for area under the plasma drug concentration‐time curve in the fed versus fasted state were 0.97 (90% CI 0.91-1.02) and 0.62 (90% CI 0.55-0.70), respectively. Levels of less than 10% conversion to the N‐desmethyl selumetinib metabolite were observed. Selumetinib was well‐tolerated, with only a few adverse events of mild intensity reported. Selumetinib administration with a low‐fat meal resulted in lower Cmax and longer Tmax for both formulations versus fasted conditions. However, area under the curve for selumetinib granules was similar under fasted and fed conditions. Overall, these findings support further development of this formulation for pediatric patients.